SISTEM INFORMASI PENDAFTARAN PULANG JAMA’AH PADA SANTRI SUKOREJODARI RAYON IKSASS KALIMANTAN - Muhammad Al Madany; Sunardi Sunardi (CV. Denasya Smart Publisher, 2025)
This study aims to design and develop an information system for the group return registration of santri (Islamic boarding school students) from Sukorejo under the IKSASS Kalimantan region. The system was developed to address the challenges of the previous manual data collection process, which was prone to recording errors and delays in information delivery. The research uses a qualitative method with data collection techniques including observation, interviews, and literature review. The system development process follows the stages of the System Development Life Cycle (SDLC), consisting of requirement, design, development, testing, and deployment. The results show that the system effectively assists administrators in managing group return data more efficiently and accurately, while also providing informative and real-time reports. With this system, administrative processes become more organized and transparent.